Error in jump height estimation using the flight time method: simulation of the effect of ankle position between takeoff and landing - Gonçalves, Carlos; Baptista, Roberto; Tufano, James; Blazevich, Anthony J; Vieira, Amilton (PeerJ, 2024)
During vertical jump evaluations in which jump height is estimated from flight time (FT), the jumper must maintain the same body posture between vertical takeoff and landing. As maintaining identical posture is rare during takeoff and landing between different jump attempts and in different individuals, we simulated the effect of changes in ankle position from takeoff to landing in vertical jumping to determine the range of errors that might occur in real-life scenarios. Our simulations account for changes in center of mass position during takeoff and landing, changes in ankle position, different subject statures (1.44-1.98 m), and poor to above-average jump heights. Our results show that using FT to estimate jump height without controlling for ankle position (allowing dorsiflexion) during the landing phase of the vertical jump can overestimate jump height by 18% in individuals of average stature and performing an average 30 cm jump or may overestimate by ≤60% for tall individuals performing a poor 10 cm jump, which is common for individuals jumping with added load. Nevertheless, as assessing jump heights based on FT is common practice, we offer a correction equation that can be used to reduce error, improving jump height measurement validity using the FT method allowing between-subject fair comparisons.
Keywords: biomechanika; pohyb; Ankle; Computer Simulation; počítačová simulace; Biomechanical Phenomena; postura těla; mužské pohlaví; hlezenní kloub; Adult; mladý dospělý; kotník; Young Adult; ženské pohlaví; Humans; Countermovement jump; Squat jump; Physical functional performance; Posture; Movement; Ankle Joint; dospělí; Computer simulation; Female; lidé; Male